(untitled) (Journal of Economic Research & Business Administration, 2015)
The article describes the performance of the republican budget for 2013-2015 from the point of view of implementation of fiscal policy. Special attention is given to the formation of the budget revenue, including tax revenues by major species and transfers in the form of budget withdrawals and budget subventions. It also provides a comparative description of the structure and directions of budgetary loans, the analysis of costs related to the acquisition of financial assets for evaluations such operations. One of the important parts of the national budget on the structure of the budget is the net lending, which is defined as the difference between outstanding and repayment of budget loans. The principle of continuity is closely interconnected with the principles of targeting and targeted nature of the budget, which assume the direction and use of tools in order to achieve performance results of each public body under their strategic plans, state and industrial programs.